The use of the Schoology digital platform for the development of online courses (Research, Society and Development, 2023)
This study aims to analyze the potential of the Schoology digital platform for offering online courses, from the point of view of students in an open course. The research is justified by the need to understand the use of different virtual learning environments. This is a qualitative research, with data obtained from the application of questionnaires. Participated in the research six students from a Distance Biological Sciences course. Most participants found the Moodle platform to be easy to use. As in the case of Moodle, most students found the environment, tools, and communication in Schoology easy to use. However, one student found it difficult to use Schoology (environment) and the tools. When asked about the greatest difficulty in the course, time was mentioned by five students. We conclude that students recognize the use of Schoology as a suitable tool for offering online courses. We also observed the need to invest in research that seeks to understand how virtual learning environments influence the success/failure of students.